The Enhancing Impact of Friendship Networks on Sales Managers’ Performance - Danny Pimentel Claro (BAR: Brazilian Administration Review, 2013)
This paper examines how relationships with friends moderate the impact of professional networks on sales performance. Based on a sample of 204 sales managers in a professional service company, this study presents evidence that friendship networks amplify the effect of sales forces’ professional networks on new product sales as well as on prospecting and converting new deals. Our results offer important insights into the socio-cognitive perspective of sales management literature and suggest that firms should encourage managers to improve their friendships in order to access valuable information that will enhance customer knowledge and support their sales efforts.